Information-Based Stock Trading, Executive Incentives, and the Principal-Agent Problem - Kang, Qiang; Liu, Qiao (Management Science, 2010)
We examine the role of information-based stock trading in affecting the risk–incentive relation. By incorporating an endogenous informed trading into an optimal incentive contracting model, we analytically show that, apart from reducing incentives, a greater risk increases the level of information-based trading, which consequently enhances executive incentives and offsets the negative risk–incentive relation. We calibrate the model and find that the economic magnitude of this incentive-enhancement effect is significant. Our empirical test using real-world executive compensation data lends strong support to the model prediction. Our results suggest that principals (boards of directors) should consider underlying stock trading characteristics when structuring executive incentives.